In vitro comparative quality study of expired and unexpired aspirin tablets available in the local market - اليوسف, غيداء; آيات عبّود (Latakia University Journal -Medical Sciences Series, 2024)
The expiry date (EXP) of a drug is the last day by which the manufacturer guarantees that the drug will retain all of its properties in terms of quality, safety and efficacy. Many studies found that in most cases, drugs do not turn into toxic products after their expiry date, but rather, their effectiveness decreases. Non-steroidal anti-inflammatory drugs (NSAIDs) are the most common drugs that expire. Aspirin is the most important and common NSAID in Syria. The purpose of this study was to compare in vitro quality study of two Syrian commercial brands of aspirin tablets before and after the expiry date. In addition, to detect the presence of salicylic acid (the major aspirin degradation product) in the studied samples. All unexpired (An, Bn) and expired (Ae, Be1, Be2) samples met the requirements which related to the external packaging and visual characterizes, except the unexpired tablets (An) which showed a clearly rough coating layer, and expired tablets (Be1) that were shiny and sticky. All unexpired and expired aspirin tablets met the USP requirements for the weight uniformity test, hardness test, friability test, disintegration test and dissolution test, except the unexpired tablets (An), which had high hardness value and failed the disintegration and dissolution tests. All expired and unexpired aspirin tablets passed the content uniformity test, except the expired tablets (Be1) which had low quantity of aspirin and unacceptable high concentration of salicylic acid. All expired and unexpired tablets of brand A (An, Ae) contained unacceptable high concentration of salicylic acid.